THE DEVELOPMENT OF OVARIAN FOLLICLE CELLS AND CORPUS LUTEUM OF MICE (Mus musculus) SWISS WEBSTER GIVEN Leucaena leucocephala LEAF EXTRACT - Wiratmini, Ngurah Intan; Sudatri, Ni Wayan; Setyawati, Iriani (International Journal of Biosciences and Biotechnology; Vol 3 No 1 (2015))
This research was conducted to determine the effect of Leucaena leucocephala leaf extract on the development of ovarian follicle cells of mice (Mus musculus). Twenty four female mice, 10 weeks old, were divided into 4 groups. The control group (P0) were given 0.9% NaCl and the treatment group P1, P2 and P3 were given 0.5, 1 and 1.5 g/ kg bw of Leucaena leaf extract, respectively. The treatments were administered daily for 15 days by gavage. After the treatment ended, all mice were dissected to collect the ovaries. Histological preparation of the ovaries used paraffin method and Hematoxylin-Eosin staining. Observations were made on the number of primary, secondary, and tertiary oocytes, and also De Graaf follicles and corpus luteum. Data were statistically analyzed using One Way ANOVA method. The results showed there were no significantly differences (P>0.05) on the number of primary, secondary, and tertiary oocytes, as well as De Graaf follicles and corpus luteum among the control and treatment groups. The mimosine content of Leucaena leaf extract was 0.87% (less than 1%) so it could not inhibit the secretion of Follicle Stimulating hormone by the pituitary gland. The doses of Leucaena leaf extract used in this research did not significantly affect the follicles development of mice ovaries. In this study, the mimosine content of Leucaena leaf extract decreased 91.8%.
Keywords: Leucaena leucocephala, mice, ovary